2021
DOI: 10.1016/j.compedu.2021.104211
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Student's live online learning readiness during the coronavirus (COVID-19) pandemic in the higher education sector

Abstract: Amid the coronavirus outbreak, many countries are facing a dramatic situation in terms of the global economy and human social activities, including education. The shutdown of schools is affecting many students around the world, with face-to-face classes suspended. Many countries facing the disastrous situation imposed class suspension at an early stage of the coronavirus outbreak, and Asia was one of the earliest regions to implement live online learning. Despite previous research on online teaching and learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
199
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(308 citation statements)
references
References 73 publications
9
199
0
20
Order By: Relevance
“…Another is to use or adapt an existing instrument (e.g. Baber 2020; Cinar, Ekici, and Demir 2021;Tang et al 2021). These two approaches are common when breaking new ground in research, but require a certain level of prior knowledge to be feasible and credible.…”
Section: Introductionmentioning
confidence: 99%
“…Another is to use or adapt an existing instrument (e.g. Baber 2020; Cinar, Ekici, and Demir 2021;Tang et al 2021). These two approaches are common when breaking new ground in research, but require a certain level of prior knowledge to be feasible and credible.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that humans will adopt technology because it is relevant. Nowadays, the pandemic has caused teachers and students to apply technology in education, which is the most convenient delivery method (Scherer, Howard, Tondeur, & Siddiq, 2021;Hofer, Nistor, & Scheibenzuber, 2021;Tang et al, 2021). Conversely, technological adoption in education creates more challenges for the users to apply advanced technology in their practice, as confirmed by Parisot (1995).…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…Participation can also be defined as taking part and joining in a dialogue for engaged and active learning. Observably, online platforms have become crucial for many people, including students (Jamalpur, Kafila, Chythanya, & Kumar, 2021;Jogezai et al, 2021& Tang et al, 2021. Students fall under three distinct groups of online platform participation: active participants, lurkers (those who read messages but do not post messages), and those who do not participate (Selma, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations